Improvements of the Aerodynamic and Thermal Characteristics of an S-Shaped Windowed HDD Arms - Ibrahim, M.D; Junaidi, E.; Osman, M.S; Khan, A.A (P Joint International Conference on Micromechatronics for Information and Precision Equipment, 2012)
Recently, hard disk drives (HDDs) having averages of 7,200 rotational per minute (rpm) are the norm. However, high-end HDDs which require higher revolutionary speed and higher track density need smart countermeasures for flow-induced vibration (FIV) such as arm vibrations; and HDDs excessive heat rise, without increasing its power consumptions. The authors propose a new actuator arm with a better window, whereby each arms in the arm actuator has a large hole with the same outer size as the original actuator arm. Another improvement that the authors propose is by creating the outer design to be a novel S-shaped design to promote better air flow in between. In this paper, the behavior of these air flows inside an HDD with the consideration of a bigger window and an S-shaped design arm actuator was studied.